PENAFSIRAN KONSTITUSI DALAM BINGKAI HUKUM PANCASILA - Andi Desmon (STIH Putri Maharaja, 2018)
Interpretive activity is an inherent activity with law and legal science. However, during this study the science of law provides a limited place to the activities of interpretation. In fact, the science of law as a practical science in charge of guiding, directing, and controlling the practical application of rational law, should be able to offer alternative solutions to legal problems, so it should provide more space for interpretation activities. Through this research, the researcher described that the interpretation of the constitution within the scope of Pancasila law. This research was normative law research. The data used in this study comes from primary legal materials, secondary legal materials, and tertiary legal materials. The legal materials, collected through literature study, and analyzed qualitatively are then presented in the form of analytical descriptive. This study concludes that in order to realize a living constitution that is responsive to societal change, the interpretation of constitutional norms must be based on the meaning of the word and its sentence structure (grammatical), historical (historical), purpose (teleological) the other positive (systematic) laws of the law, and contextually referring to social and economic (sociological) factors with reference to fundamental (philosophical) cultural and humanitarian values (predictions) for future (futurological). The principles and content of Pancasila as a limitation or restriction in the interpretation of the constitution is a necessity for the future of Indonesia, as aspired in the Preamble to the 1945 Constitution.